Penerapan Model Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Analitis Siswa pada Pembelajaran Matematika : The Application of the Problem-Based Learning Model to Enhance Students' Analytical Thinking Skills in Mathematics Learning - Fauziah, Ana (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the application of the Problem-Based Learning (PBL) model in enhancing students' analytical thinking skills in mathematics. The research method employed was a quasi-experiment with a pretest-posttest control group design. The study population consisted of eighth-grade students at MTs Darul Iman Pandeglang, with a sample of 60 students divided into two groups: an experimental group and a control group, each comprising 30 students. Research instruments included an analytical thinking skills test, observation sheets, and a student response questionnaire. Data were analyzed using an independent samples t-test and N-Gain analysis. The results indicated that the application of the PBL model significantly enhanced students' analytical thinking skills, with a calculated t-value of 3.847 > t-table of 2.045 at a significance level of 0.05. The improvement in the experimental group's analytical thinking skills yielded an N-Gain score of 0.72, categorized as high, whereas the control group obtained an N-Gain score of 0.31, categorized as moderate. Student responses to the PBL model were positive, with a percentage of 82.3%. Thus, the PBL model is proven effective in enhancing students' analytical thinking skills in mathematics learning.